AB0754 Persistence Rate with Subcutaneous Biologic Therapies in Patients with Ankylosing Spondylitis (AS). (9th June 2015) - Lyu, R.; Ding, Q.; Govoni, M.; Makin, C.; Korn, J.; Fan, T.; Ogbonnaya, A.; Black, C.M.; Kachroo, S.
Abstract : Background: The treatment landscape of rheumatoid diseases has evolved in recent years, with the introduction of subcutaneous TNF-alpha blockers in the EU. These changes in the rheumatoid disease treatment landscape could affect how patients are managed with rheumatoid diseases. Objectives: This study aimed to describe persistence with subcutaneous biologics among biologic naïve AS patients over 12 months, and to identify differences among patients with and without NSAID drug experience. Methods: This retrospective study used IMS Disease Analyzer-Germany, an electronic medical records database. Data for adult (≥18 years of age) AS patients with a prescription for subcutaneous biologic between January 1, 2009 and June 30, 2012 were used for this analysis. The index date was the date of the first subcutaneous biologic prescription. Prescription for any biologic during the pre-index period or diagnosis for rheumatoid arthritis, psoriatic arthritis or other conditions treated with subcutaneous biologics either in pre- or post-index qualified patients for exclusion from the study. Differences between pre -index NSAID naïve and experienced patients were measured using a chi-square test. A logistic regression model was used to further assess the impact of NSAID use on persistence, controlling for baseline characteristics. Results: The study cohort included a total of 108 biologic naïve AS patients, 72 with use of NSAIDs in the pre-index period. The mean age of the AS cohort was 42 years, with 70% of patients being male. Adalimumab, etanercept, and golimumab were initiated by 61%, 28%, and 11% of patients, respectively. Persistence for at least 12 months with the index subcutaneous biologic was observed in 46.3% of the overall cohort, with similar results among those with and without NSAID use (47% vs 44%, respectively). Multivariate analysis confirmed similar persistence between those with and without pre-index NSAID (OR: 0.97; 95% CI: 0.39-2.44). Conclusions: Findings from this German study showed that less than half of AS patients are persistent with the index subcutaneous biologic over a 12 month period. Results were similar irrespective of prior use of NSAIDs. Disclosure of Interest: R. Lyu Employee of: Merck, Q. Ding Employee of: Merck, M. Govoni Employee of: Merck, C. Makin: None declared, J. Korn: None declared, T. Fan Employee of: Merck, A. Ogbonnaya: None declared, C. Black Employee of: Merck, S. Kachroo Employee of: Merck